Zaydi Discriminatory Decrees and Their Effect on Yemenite Jews in Nomi Eve’s Henna House - Alwuraafi, Ebrahim (LPPM Universitas Advent Indonesia, 2021)
Nomi Eve’s novel Henna House: A Novel (2014) is the first novel to tackle the history of Jews in Yemen—one of the poorest and most forgotten countries of the world—in English. The novel revisits the last period of the Jews’ history in Yemen before their transportation to Israel in Operation Magic Carpet between 1949 and 1950 and is illustrative of the subordination and suffering of Jews in Yemen. It explores the experience of the Yemenite Jews in the first half of the twentieth-century Yemen and reveals the explicitly racialized association of human repression of Zaydi majority. It also explores the experiences of marginalization and segregation in the lives of Yemenite Jews. It raises questions on the relation between religion, politics and minorities and legal implications of the incorporation of a religious minority into the mainstream of national identity. The aim of the present article is to examine the effects of Zaydi discriminatory laws particularly the Orphans’ Decree on the Yemenite Jewish community and explores the experience of the Jewish children under the threat of being uprooted just to be planted in another soil. It argues that Eve has been able to articulate the suffering experienced by Yemenite Jews at the hands of Zaydis and that the novel presents a realistic picture of the Jewish community during the first half of the 20th century.